PENGARUH PEMBERIAN FERMENTASI DARI UMBI UBI KAYU DALAM RANSUM TERHADAP PENAMPILAN AYAM PEDAGING - Novita Herdiana (Jurnal Penyuluhan Pertanian, 2020)
The purpose of this experiment was looking for effect of level fermentation root cassavaon broiler ration to performance. Fermentation root cassava level in ration consisted of 0%,5%, 10%, 15% and 20%. The experimental design of this research was CompletelyRandomized Design consisted of five treatments with four replications.The result of the experience showed the using of 20% fermentation root cassava in theration not significant different to the final body weight,conversion ration and components ofcarcass.